Analyses of the Department of Defense Acquisition Workforce Update to Methods and Results through FY 2011 - Gates, Susan M. (RAND Corporation, 2013)
The organic defense acquisition workforce oversees defense acquisition programs from start to finish. RAND has been providing ongoing analysis of the workforce. This volume documents revisions to methods summarized in an earlier report, describes the workforce through fiscal year 2011, and provides a user's manual for a model for projecting workforce needs through 2021 under different assumptions about the future.